Epidermolytic ichthyosis and rickets. Case report. - Perosa, A.; Sardella, L.; Acquafredda, A.; Mazzotta, F.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2004)
A case of rickets due to vitamin D deficiency in a 3-year-old little girl with epidermolytic ichthyosis is reported. Her mother was also affected by epidermolytic ichthyosis and followed by one of us. To the best of our knowledge, this is the first case of rickets in a subject with epidermolytic ichthyosis.